The ethics of care for the good of the common house - Diaz, Juan Carlos (2017)
The Democratic institutions are founded on a series of painful political experiences, like the holocaust, from which we have gained an important learning. However, the culture of human rights needs to strengthen within the regards of an ethic of memory, that conveys the efforts of the entire society so it can identify liabilities in a context of violence. This ethical reflection prevents the causes of violence from appearing again, but also guides us in the search for new parameters about our conceptions of a meaningful life. Thus human development is part of this same democratic process whose objective is the formation of a sense of justice that allows us to genuinely care about the other.